1975
DOI: 10.1021/ja00848a015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of base promoted reduction of nickel(III) complexes of macrocyclic amines. Coordinated ligand radical intermediate

Abstract: The mechanisms of decomposition of two nickel(III) complexes which contain macrocyclic secondary amine ligands have been studied. When 2 is treated with basic solvents such as pyridine, triethylamine, or water a Ni(II) ligand radical species is formed according to:Chemical and spectroscopic evidence is presented in support of this species. A similar species is observed in the decomposition of 4 by pyridine but is not observed in water although product analyses suggest that a radical species is again formed. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 3 publications
2
28
0
Order By: Relevance
“…In light of the recent work on the base catalysed decomposition of Ni(II1) macrocycles (16)(17)(18)(19)(20) the results of the present work can best be explained by the following general mechani~m.~ 'The proton could also be lost from the nitrogen next to the carbon containing 2 methyl groups to give another isomer of 3. Likewise the radical in 4 could, and very likely is, also on the other nitrogen.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…In light of the recent work on the base catalysed decomposition of Ni(II1) macrocycles (16)(17)(18)(19)(20) the results of the present work can best be explained by the following general mechani~m.~ 'The proton could also be lost from the nitrogen next to the carbon containing 2 methyl groups to give another isomer of 3. Likewise the radical in 4 could, and very likely is, also on the other nitrogen.…”
Section: Discussionmentioning
confidence: 67%
“…After this work was begun Barefield and Mocella reported that the base catalyzed decomposition of the same complex proceeded via a Ni(I1)-ligand radical (16). Later several Ni(II1) macrocyclic complexes, including 2, were generated by pulse radiolysis and their decomposition studied (17)(18)(19)(20).…”
Section: +Imentioning
confidence: 99%
See 3 more Smart Citations